Leaf beetles employ tryptophan to detoxify the chemical defenses of poplar trees - Xingrong Peng; Michael Reichelt; Ana Patricia Baños-Quintana; Beate Rothe; Felix Feistel; Martin Kaltenpoth; Jonathan Gershenzon; Sybille B. Unsicker (Proceedings of the National Academy of Sciences, 2025)
Herbivorous insects have evolved many fascinating adaptations to overcome the chemical defenses of their host plants. This study employed targeted and untargeted metabolomics, coupled with isotope labeling, to shed light on the metabolism of salicinoids—potent antiherbivore phenolic defenses present in the Salicaceae family—in the poplar-specialized leaf beetle, Chrysomela tremulae . C. tremulae was found to produce a range of metabolites from salicortin and utilize the essential amino acid tryptophan and its breakdown products, namely kynurenine, kynurenic acid, and 4-hydroxyquinoline, to form novel conjugates with the salicinoid metabolite saligenin, which are then excreted in the feces of the beetles. Saligenin and its conjugates are not toxic to C. tremulae and similar metabolic pathways were found in other poplar herbivores. Experimental analyses of the gut microbiota revealed that there is no microbial contribution to the formation of tryptophan metabolite–saligenin conjugates. The production of such substances by insect herbivores may be a critical adaptation that enables specialists to survive on a diet high in salicinoid defense compounds. Therefore, identifying the underlying detoxification mechanisms creates opportunities to develop targeted anti-insect agents for protecting salicaceous trees.